PENGEMBANGAN KONSEP OPEN GOVERMENT UNTUK MENINGKATKAN KUALITAS LAYANAN KOTA PALEMBANG (STUDI KASUS : KOTA PALEMBANG) - Tri Akhyari Romadhon; M. Izman Herdiansyah (Gema Teknologi, 2021)
Open Government is committed to improving the quality of information availability on government activities, supporting civil society participation in government, upholding professional standards in public administration to prevent corruption, abuse of power and increasing access to the use of new technologies to support accountability and openness. Currently, many governments have implemented e-government which supports the government's goals in open government. Where, e-government is used to describe the use of technology in carrying out several government tasks. The city government of Palembang has several applications or e-government systems that are open government. The city government of Palembang has not made a quality measurement of the e-government that has been implemented, so it is not known the level of quality in each application or system implemented. Based on this explanation, it is necessary to analyze the level of service quality in the system that has been implemented by the Palembang City Government.